Genetics of Familial Infantile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Four families from northwestern France with autosomal dominant benign infantile convulsions and paroxysmal choreoathetosis were studied genetically by linkage analysis at the Wellcome Trust Centre for Human Genetics, University of Oxford, UK, and at Genetic Clinics in Amiens, France.